Ilustration Style in Balinese Childdren’s Song Animation - Arya Janottama, I Putu; Artha, Agus Indram Bayu (Institut Seni Indonesia Denpasar, 2023)
This article is a study to support the pre-production process of animation that takes the theme of Balinese children's songs. Studies that discuss the visualization of illustrations in animated Balinese children's songs are still rarely, even though Balinese children's songs are one of the most sought-after content on Youtube social media. The urgency of this research lies in the existence of animated visualizations that tend to follow the style of outside Bali causing the audience's representation of Balinese identity to shift. With the rapid development of digital media, the space for displaying animation is unlimited, and can be accessed from various places. This article aims to provide references and suggestions for traditional Balinese styles that can be developed as a reference in the animation pre-production process. Data obtained through observation, documentation, and literature, then analyzed to obtain a synthesis, namely the style of illustration design for animation production. Based on the data obtained, there is still a visual style of Balinese children's song animation that tends to follow the western style or minimalist style due to the lack of character deepening and manufacturing techniques. In conclusion, the animation of Balinese children's songs using Balinese illustration style needs to pay attention to Balinese visual styles such as Ubud, Batuan, and Kamasan, as a reference. This visual style can later be applied starting from the script, scene, character design and also the background that dominates the animation visualization.